Baculovirus-free insect cell expression system for high yield antibody and antigen production - Janin Korn (Nature Portfolio, 2020)
Abstract Antibodies are essential tools for therapy and diagnostics. Yet, production remains expensive as it is mostly done in mammalian expression systems. As most therapeutic IgG require mammalian glycosylation to interact with the human immune system, other expression systems are rarely used for production. However, for neutralizing antibodies that are not required to activate the human immune system as well as antibodies used in diagnostics, a cheaper production system would be advantageous. In our study, we show cost-efficient, easy and high yield production of antibodies as well as various secreted antigens including Interleukins and SARS-CoV-2 related proteins in a baculovirus-free insect cell expression system. To improve yields, we optimized the expression vector, media and feeding strategies. In addition, we showed the feasibility of lyophilization of the insect cell produced antibodies. Furthermore, stability and activity of the antibodies was compared to antibodies produced by Expi293F cells revealing a lower aggregation of antibodies originating from High Five cell production. Finally, the newly established High Five expression system was compared to the Expi293F mammalian expression system in regard of yield and costs. Most interestingly, all tested proteins were producible in our High Five cell expression system what was not the case in the Expi293F system, hinting that the High Five cell system is especially suited to produce difficult-to-express target proteins.